Cassia javanica, Pink and White Shower - Michael G. Andreu; Melissa H. Friedman; Robert J. Northrop (EDIS, 2012)
Cassia javanica is a deciduous tree native to Southeast Asia and Indonesia. This tree is referred to as “pink and white shower” because it produces pink and white blooms. It is also called “apple blossom cassia” because its dainty pink and white flowers may be easily confused with those of apple trees. It is planted primarily as a decorative shade tree. This 2-page fact sheet was written by Michael G. Andreu, Melissa H. Friedman, and Robert J. Northrop, and published by the UF/IFAS School of Forest Resources and Conservation, July 2012.